2012
DOI: 10.1159/000338682
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 1 Pro198Leu Polymorphism in Brazilian Alzheimer’s Disease Patients: Relations to the Enzyme Activity and to Selenium Status

Abstract: Background/Aims: Oxidative stress plays a central role in Alzheimer’s disease (AD). Pro198Leu cytosolic glutathione peroxidase (GPx1) polymorphism seems to be associated with a lower activity of this enzyme, but there are no studies with AD patients. Thus, the aim was to determine the frequency of the GPx1 Pro198Leu polymorphism in AD patients and to verify its relation to glutathione peroxidase (GPx) activity and selenium (Se) status. Methods: The study was carried out in a group of AD elderly (n = 28) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
2
17
0
1
Order By: Relevance
“…Meta-analysis including data of Wiener et al and ours could not be conducted due to lack of raw data in Wiener's publication. Similarly to Cardoso et al [7] we did not find any association between rs1050450 of the GPx-1 gene and AD risk.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Meta-analysis including data of Wiener et al and ours could not be conducted due to lack of raw data in Wiener's publication. Similarly to Cardoso et al [7] we did not find any association between rs1050450 of the GPx-1 gene and AD risk.…”
Section: Discussionsupporting
confidence: 86%
“…There are only few studies evaluating the importance of ADS gene single nucleotide polymorphisms (SNPs) as risk factors of AD. So far, there were two studies evaluating the significance of one SNP of the catalase gene (rs1001179) [4,5], one -the significance of four SNPs of the SOD2 gene (rs2758346, r4880, rs2855116 and rs5746136) [6] and another one evaluating the significance of the rs1050450 SNP of the GPx-1 gene [7]. Only the study on the SOD2 gene, yielded positive results.…”
mentioning
confidence: 99%
“…A study of the Ecuadorian population (Paz-y-Mino et al 2010) showed that the Gx1-Leu allele increased the risk of AD. Interestingly, Cardoso et al did not observe a difference in the genotypic frequency between AD patients and the control groups in a Brazilian population (Cardoso et al 2012). However, a case-controlled study on the association of GPx-1 and…”
Section: Discussionmentioning
confidence: 92%
“…There is considerable evidence that GPx has a strong association with some diseases, many with links to the DA system (Bai et al 2017;Cardoso et al 2012;Gardaneh et al 2011;Paz-y-Mino et al 2010;Power and Blumbergs 2009). In fact, DA is a major source of ROS in the central nervous system, as it can produce ROS and DA-quinone during its autooxidation (Zucca et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cardoso et al (2012), ao determinar o polimorfismo em um grupo de 28 idosos com doença de Alzheimer, observaram que 75% apresentaram genótipo Pro/Pro, 14% de heterozigotos e 11% de Leu/Leu. No mesmo estudo, no grupo controle, formado por 29 idosos sem a doença, os pesquisadores encontraram 72% com genótipo Pro/Pro, 14% de Pro/Leu e 14% de homozigotos Leu/Leu.…”
unclassified